Atención al cliente en la Empresa Dismero S.A del cantón Montalvo. - Ramos Cepeda, Karina Elizabeth (2022)
The present case study was carried out in the company Dismero S.A of the Montalvo canton, it is a supermarket that started 5 years ago in the commercial activities of the canton, offering varieties of massive products at affordable prices, it is currently the most visited supermarket by consumers due to which they express that they have very convenient costs for users, however, one of the drawbacks is the dissatisfaction of customer service by employees since they are not cordial, attentive and helpful, therefore their lack of training in how to treating or helping customers lead to a bad image of the supermarket, since customer service is definitely an essential component for any company. One of the main reasons for which the employee does not perform his function well in customer satisfaction is due to the lack of motivation since his work environment is also not harmonious and by ignoring the needs of consumers, he provides a bad service experience and this results in the loss of customers who will go to the competition. That is why every company must be very clear that it is essential to listen to the needs of its customers since there are many factors that affect the attention of consumers, whether it is the skills of the employees or the expectations they hope to obtain with the supermarket, always keeping in mind that the consumer lies in the success of a company.